Transisi Peradaban: Kajian Kualitatif tentang Stagnasi Intelektual Islam dan Renaisans Barat - Saputra, Junifer; Erman, Erman; Hasnah, Radhiatul (UNIVERSITAS SERAMBI MEKKAH, 2025)
During the Abbasid Dynasty, Islamic civilization and culture grew and developed and even achieved glory. This was because the Abbasid Dynasty in this period emphasized the development of Islamic civilization and culture more than the expansion of territory. The peak of the Abbasid Dynasty's glory occurred during the time of Caliph Harun Ar-Rashid (786-809 M) and his son Al-Makmun (813-833 M). However, after this period, the Islamic world experienced intellectual stagnation that led to a decline in various fields where science and philosophy that had previously flourished began to be considered a threat to faith. As a result, the door to ijtihad was closed, the tradition of critical thinking and intellectual freedom came to a halt. Meanwhile, the Western world entered the Renaissance era (14th to 17th centuries) which marked an intellectual, cultural, and scientific renaissance. This article aims to analyze the factors that led to intellectual stagnation in the Islamic world and how the Western world managed to rise through the Renaissance. This research uses a qualitative approach with a literature study method. Data sources were obtained from a review of primary and secondary literature, including historical texts, scholarly works, and relevant documents. The analysis is done descriptively to understand the factors that contributed to the intellectual stagnation of Islam and the rise of the Western Renaissance.